Reducing the electronic band gap of BN monolayer by coexistence of P(As)-doping and external electric field. (January 2020) - Hoat, D.M.; Naseri, Mosayeb; Ponce-Pérez, R.; Hieu, Nguyen N.; Vu, Tuan V.; Rivas-Silva, J.F.; Cocoletzi, Gregorio H.
Abstract: Boron nitride (BN) monolayer (ML) has been the subject of many investigations, however, its large electronic band gap has limited so much its applications. Therefore, the band gap engineering is a necessary step at the time of designing practical uses of the BN ML to extend its applicability to nano-optoelectronic devices. In this work, we investigate systematically the impact of P- and As-doping as well as an external electric field on the electronic structure of BN ML using first-principles calculations based on the pseudopotential density functional theory. Results indicate that the pristine BN ML has an indirect K − Γ band gap of 4.589 eV. The N-substitution by P and As induces a band gap reduction of the order of 19.50% and 22.29%, respectively. Additionally, the external electric fields with strength in the range of −0.5 to 0.5 (eV/Å/e) are applied along the z-axis perpendicular to the MLs for both upward and downward directions. Under a weak electric field ± 0.1 (eV/Å/e), the electronic band gap of all three considered monolayers does not show a significant change. However, a stronger electric field will decrease considerably this parameter. Our results confirm that the coexistence of doping and external electric field can be a quite efficient approach to fine-tune the electronic structure of BN ML. Highlights: BN monolayer has a graphene-like honeycomb planar structure. P- and As-doping induces a local structural distortion. Pristine BN monolayer is an indirect semiconductor with band gap of 4.589 eV. The electronic band gap decreases considerably under both doping and external electric field presence effect.